A dinâmica das águas e das gentes: história, políticas públicas e percepção de riscos no Acre - Domingos José de Almeida Neto (2015)
Among the various challenges faced by the occupants and non-indigenous creators of the Acre territory past or present it is certainly those related to sanitation and health that are most emblematic. This is especially true when one analyzes the most vulnerable parts of the population in environmental, political, socioeconomic and cultural terms. In this respect, the present thesis aims to describe the dynamic between water and the Acrian people with respect to public policies and the perception of risks in Acre. It does not, however, present a complete and linear history of this theme. Rather, it dicusses a few important periods that will be discussed in the form of articles. These were elaborated in distinct time-spaces and are organized in the following two parts: Part One (Formation of the territory: population, health and sanitation) Article 1: Health and environment in the rubber plantations of Bolivian Acre (1870-1903): the role of exogenous factors and processes; Article 2: Between [the] Chagas and [the] Cruz: the position of Manguinhos scientists against the States actions in malaria-infested rubber producing zones in Amazon-Acre (1912-1913); Article 3: The sanitation era in Brazil (1910-1930) and its reflections in the Federal Territory of Acre. Part Two (The capital and its waters: population, environment and public policies) Article 4: Which is riskier: life on the floodplain or in housing imposed from above? The case of flooding regions in Rio Branco, Acre, Brazil; Article 5: Back and forth between water and people: perception of risks and public policies in flood-prone districts of Rio Branco, Acre; Article 6: Threat, exposition and vulnerability: an analysis of the 2015 flood in Rio Branco in light of the risk triangle. The theoretical base of the articles is founded in the comprehension of risk. For the articles in the first part, the perception of risk is generally associated with the economic process of rubber production from the native Acrian plantations for the health-sickness of the producer. For the articles in the second part, the discussion of risk adopts a stance more concerned with environmental justice, considering that it is in the unequal dispute for typically urban soil that the poor end up occupying areas considered unfit to establish housing. These articles have a base in qualitative methodology. The research used three main techniques: literature, individual semi-structured interviews and non-participant observation, in addition to the use of content analysis to accentuate the effectiveness of the previous techniques. Despite each article having its own objective, it can be seen that the series of research projects that founded them outlined the following main findings regarding public policies and the perception of risks in Acre: exogenous factors and processes play a significant role; different social classes have different weights; the notion of risk possesses different meanings for technical and non-academic knowledge bases; for flood-prone territories, the predisposition of the public authority is to remove inhabitants to Social Interest Housing; issues regarding inhabitants socioeconomic and cultural situation in flood-prone territories influences their acceptance or non-acceptance of population removal policies.